Judas’ Proskynesis - Rzepka, Jacek (The Biblical Annals, 2024)
The present article starts from an observation that Mark and Matthew use two different, though cognate words for Judas’ kiss (philein and kataphilein). Kataphilein is omitted from Luke’s passion narrative, while Judas’ kiss as such is absent from John. A closer look is offered at the verb kataphilein in Classical contexts, where it may be synonymous with proskynein (‘to perform a ritual prostration’). It is suggested that what Judas actually performed at Gethsemane was technically proskynesis. Judas’ gesture, perhaps imitated by some of his armed accomplices, was rendered as an unwilling act of reverence to Jesus by some of Judas’ companions in John. It is further argued that the Gethsemane proskynesis was orchestrated in collusion with the temple elites that needed firm evidence of Jesus’ revolutionary activity to obtain the Roman governor’s consent to put Jesus to death (they previously had tried to entrap him in the taxation discourse). As a Roman military unit was present at the arrest of Jesus, Pilate had now several Roman witnesses of the royal style of Jesus, and was forced to act together with the temple elite. This reconstruction speaks for complementarity of the passion narratives in spite of differing highlights of the four evangelists.